2014
DOI: 10.1007/s13277-014-2952-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of ibuprofen on tumor survival and angiogenesis in gastric cancer cell

Abstract: Numerous epidemiological studies have suggested effectiveness of long-term and regular use of non-steroidal anti-inflammatory drugs (NSAIDs), such as ibuprofen and aspirin, in preventing and treatment of certain cancers including prostate, colon, breast, lung, and gastric cancers. We have studied the potential anti-turmeric effect of ibuprofen in adenocarcinoma gastric cell line (AGS). The effects of ibuprofen were investigated on cell proliferation, apoptosis, angiogenesis, and expression of stemness marker g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…Our observations on the inhibitory effect of ibuprofen on cell proliferation were consistent with the observations made in our previous study on the gastric cancer cell line that treated with ibuprofen and as a result, cells had decreased proliferation, entirely similar to our current results (Akrami et al, ), also our results were in agreement with other studies on anti‐cancer effect of ibuprofen (Bonelli et al, ; Thakkar et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observations on the inhibitory effect of ibuprofen on cell proliferation were consistent with the observations made in our previous study on the gastric cancer cell line that treated with ibuprofen and as a result, cells had decreased proliferation, entirely similar to our current results (Akrami et al, ), also our results were in agreement with other studies on anti‐cancer effect of ibuprofen (Bonelli et al, ; Thakkar et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our previous study as well as many other studies have proved NSAIDs are probably able to prevent the initiation and proliferation of several tumors including gastric cancer (Akrami et al, ; Bonelli et al, ; Piazuelo and Lanas, ), besides the availability and high use of ibuprofen nowadays and other NSAIDs make it easier to study their effects on cancer cell signaling (Piazuelo and Lanas, ). Hence, the main purpose of our work was to explore the effect of ibuprofen on tumorigenicity, proliferation and the expression of relevant genes in Wnt signaling pathway in GCSCs derived from MKN‐45 and AGS cell lines.…”
Section: Discussionmentioning
confidence: 73%
“…[15] Numerous studies have suggested that aspirin and/or other NSAIDs can be effective in the prevention and/or treatment of malignancies, such as cancers of the colon, [16] breast, [17,18] lung, [19] pancreas, [20] prostate, [21,22] ovarium, [23] squamous cell carcinoma and melanoma, [24] etc. Different NSAIDs have been reported to inhibit the growth and survival of cell lines established from a wide variety of cancers, including gastric cancer, [25,26] cancers of the colon, [27] lung, [28] urinary bladder, [29] osteosarcoma, [30] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ip (IBF anion) (0.9015 eV) and Ea (guanine cation) is the electron affinity of guanine cation being equal to 6.5582 eV, Table 2, then the electron transfer energy equals to −6.08613 eV taking in our consideration the columbic potential energies of the IBF anion and guanine cation. The negative sign of the electron transfer energy means that the electrons come spontaneously from the mixture of IBF anions and the conjugate IBF molecules to guanine cations strongly, hence the strong spontaneity of the electron transfer from the IBF anions to the cationic guanine in the carcinogenic cell in the intestine and blood gives the chance to inhibit different types of cancers as colon, protostate, lung and breast cancers, [2] [3] [4]. The calculations of the S and R forms are consistent and it is enough to do the calculations with one of them which is S-form, moreover, it has been concluded that the bioactive isomer of IBF is the S-form as reported by Naveen Chhabra et al [6].…”
Section: Anticancer Effect Of Ibuprofen Drugmentioning
confidence: 99%
“…ibuprofen drug is one of the classes of drugs known as non-steroidal anti-inflammatory drugs (NSAIDS), with moderate anti-inflammatory, analgesic, and antipyretic activity. Recently, the regular use of ibuprofen prevents from some certain cancers including prostate, colon, breast, lung, and gastric cancers due to the inhibition of cyclooxygenase-2(COX-2), [2] [3]. Ibuprofen reduces risk of human lung cancer by selective cyc-looxygenase 2 (Cox-2), [4].…”
Section: Introductionmentioning
confidence: 99%